Upaya Iran Green Movement dalam Menekan Pemerintah Iran untuk Mengimplementasikan Hak Perempuan melalui New Media - Nadia Widianti; Reni Windiani; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Iran Green Movement is one of the historical events in Iranian politics. Starting from the claim of fraud in the 2009 presidential election, but eventually rooted in other problems. One of them is the demands of Iranian women against several policies that were considered discriminatory during the Ahmadinejad administration. To carry out their agenda, the demonstrators of the Iran Green Movement use the existence of new media which is claimed to play a significant role in pressuring the government to implement some of the demands put forward by the community, especially women. This is because the use of new media is easy so it can be accessed by anyone without any interference from the political elite. By using the concept of new media from Everett Rogers, this study discusses the efforts made by the demonstrators through the use of new media as the main tool in the process of running the Iran Green Movement agenda. The result of this study is that new media platforms such as Twitter, YouTube, and the Web play an important role in mobilizing the masses, forming public spaces, gaining massive support, and disseminating information to the public. Although the objectives of the Iran Green Movement agenda were not fully successful, the involvement of the new media had a significant influence and impact on Iranian politics. For further research, it is recommended to discuss about social networking in the involvement of new media in an event